1984
DOI: 10.2307/3281395
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Trematode Uvulifer ambloplitis on Juvenile Bluegill Sunfish, Lepomis macrochirus: Ecological Implications

Abstract: The JSTOR Archive is a trusted digital repository providing for long-term preservation and access to leading academic journals and scholarly literature from around the world. The Archive is supported by libraries, scholarly societies, publishers, and foundations. It is an initiative of JSTOR, a not-for-profit organization with a mission to help the scholarly community take advantage of advances in technology. For more information regarding JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
117
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(130 citation statements)
references
References 23 publications
8
117
5
Order By: Relevance
“…Other freshwater fish species show increased mortality when infected with neascus-type metacercariae, possibly due to increased predation susceptibility (Esox lucius, Harrison and Hadley 1982; Chasmistes brevirostris, Markle et al 2014). Reported sub-lethal impacts of neascus-type infection vary greatly from no effect on salmonid metabolism and growth (Ferguson et al 2012) to significant weight loss at high levels of parasite load in Centrarchids (e.g., Micropterus dolomieu, Hunter and Hamilton 1941; Lepomis macrochirus, Lemly and Esch 1984). In our study, heavily parasitized steelhead felt rough to the touch (CJS, personal observation), suggesting a possible loss of streamlining and increased swimming burden.…”
Section: Water Temperature and Trematode Activitymentioning
confidence: 99%
“…Other freshwater fish species show increased mortality when infected with neascus-type metacercariae, possibly due to increased predation susceptibility (Esox lucius, Harrison and Hadley 1982; Chasmistes brevirostris, Markle et al 2014). Reported sub-lethal impacts of neascus-type infection vary greatly from no effect on salmonid metabolism and growth (Ferguson et al 2012) to significant weight loss at high levels of parasite load in Centrarchids (e.g., Micropterus dolomieu, Hunter and Hamilton 1941; Lepomis macrochirus, Lemly and Esch 1984). In our study, heavily parasitized steelhead felt rough to the touch (CJS, personal observation), suggesting a possible loss of streamlining and increased swimming burden.…”
Section: Water Temperature and Trematode Activitymentioning
confidence: 99%
“…Other studies have described a similarly high prevalence (e.g. Evans & Mackiewicz 1958, Lemly 1980, Lemly & Esch 1984, Ferrara & Cook 1998. Although prevalence of infection in one species can be high, it can be variable among species in the same system.…”
Section: Discussionmentioning
confidence: 95%
“…However, some studies have indicated that black spot agents can result in reduced survival, growth, and health of fishes in natural systems. For instance, Lemly & Esch (1984) found that bluegills Lepomis macrochirus infected with Uvulifer ambloplites had reduced lipid concentrations and lower body condition relative to those without infection, resulting in higher overwintering mortality of infected fish compared with that of non-infected fish in a North Carolina pond. Harrison & Hadley (1982) suggested that reduced growth and survival of northern pike Esox lucius in the Niagara River, New York, resulted from black spot infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations